(untitled) (REMUNOM, 2025)
In Teresina-PI, where most of the city is situated between the Poti and Parnaíba rivers, the use of sand in concrete production has become a common practice. However, the quality of the sand used for concrete mixing is often unsatisfactory, with a fineness modulus below the standard established by ABNT (Brazilian Association of Technical Standards). The lack of specific studies, the absence of proper beneficiation, the lack of technical knowledge in the area, and incorrect usage have led to the rejection of "massará" by civil construction professionals and a large part of the Teresina population. This situation has resulted in the material becoming obsolete and losing value in the regional market. This study aims to mechanically characterize concrete using washed "massará" as fine aggregate instead of sand, maintaining the same proportions of aggregates, water, and cement as conventional concrete. The cement used is CP IV-F 40, the same type employed in large concrete plants in Teresina. Granulometry tests, slump cone tests, and axial compression tests on cylindrical specimens were conducted. The test results showed that washed "massará" exhibits compression strength similar to that of conventional concrete, demonstrating its viability as an alternative fine aggregate in concrete production. This study suggests a new alternative for concrete mixing, especially considering the increasing scarcity of aggregate deposits due to high market demand.